(3QSGdI GdCfhGQ GdbOSjIs - (3Gdbej, eMeO SYjO GdTQja, cGf MjG aj SfI (B1099(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj BJGfG GdMceI cj fJhUd HgG Edi eG dOjg(B...(3aGdabjQ Edi Gddg GdZfj(B...(3eMeO(B...(3CajVJ Ydi QhMj HYV ChbGJ GdePGcQI CKHJgG cj jfJaY HgG(B...s
(3BNQgG (B:s
...(3hEjGc hCf JSJHYO(B...(3aj gPg GdeQGJH CheG OQjJ Cf GdYGde cdg(B...s
(3CJe JCdjag aj (B1 (3eMQe (B1085(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B603s
(3GdPQjYI(B:(3L(B16(3,U(B398(3, JMJ Qbe (B1581s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds